Exchange of Information and Expertise 1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Martin Desire Abega, Association Terre et Développement, Ngoumou, Cameroon: 'We are a young NGO concerned with rural development in the Mefou Akono regions of Central Province. We have a number of experiences which we would like to share and ask...